Development of Interactive Learning Media Using Lectora Inspire Oriented towards Critical and Creative Thinking Skills on Simple Harmonic Motion - Putri Nabila; Fanny Rahmatina Rahim; Silvi Yulia Sari (Universitas Lambung Mangkurat, 2023)
This study uses the Lectora Inspire application to develop interactive learning media oriented towards critical and creative thinking skills on valid simple harmonic motion topics. Research and Development (R&D) was employed in this study. The ADDIE model was used (analyze, design, development, implementation, evaluation). The instruments used in this study consisted of needs analysis instruments, student characteristics instruments, and validity instruments. The data analysis techniques used were needs analysis and validity analysis. Based on the study, the product validity value averages 0.83 for the very valid category. This demonstrates that the developed interactive learning media meets users' requirements (teachers and students).